DAMPAK PEMBANGUNAN JALAN TOL TRANS JAWA TERHADAP PELUANG KEWIRAUSAHAAN - Nouri, Mh Nateq; Gugun Muhammad, Fauzi; Muhammad Daffa, Musyary (PENDIDIKAN SAINS DAN TEKNOLOGI, 2024)
The National Medium-Term Development Plan (RPJMN) for 2015-2019 and RPJMN for 2020-2024 emphasizes infrastructure development as the key to accelerating economic growth, especially through the implementation of a 2,500 km new toll road construction program. This program includes monumental projects such as the Trans Java Merak-Banyuwangi and Cikampek-Palimanan (Cipali) toll roads, which are the longest toll roads in Java. Evaluation of toll road development, in accordance with Government Regulation (PP) No. 39/2006, is a crucial step in assessing the success of public policy. However, PP No. 15/2005 emphasizes that the purpose of highway projects is to support economic growth and equitable development. In-depth research focused on the impact of the Trans Java toll road on economic growth in East Java. The results show the complexity and variation in the impact, with some toll roads increasing economic growth, while others decrease it. While theory suggests that infrastructure can accelerate economic growth, toll road development in East Java does not have an overall positive impact. Factors such as poor accessibility, high toll fees, and a lack of supporting infrastructure may be to blame. This impact is reflected in the decline in East Java's economic growth from 9.87% to 4.34% two years after toll road construction.